[PP.28.12] 24-HOUR PATTERNS OF CENTRAL AORTIC AND BRACHIAL SYSTOLIC BLOOD PRESSURE IN THE VERY ELDERLY. (September 2016) - EZHOVA, N.; Alam, A.; Kotovskaya, Y.; Kobalava, Z.
Abstract : Objective: The aim of current study was to investigate and compare 24-hour profiles of central and peripheral blood pressures in the very elderly via their simultaneous ambulatory monitoring. Design and method: Parallel 24-h ambulatory aortic and brachial blood pressure monitoring was performed in 67 treated hypertensive subjects older than 80 years (mean age 84, 1 ± 3, 1 years, 25, 5% male, mean clinic brachial SBP 134, 8 ± 23, 2 mmHg) with an oscillometric cuff-based device BPLab Vasotens («Petr Telegin», Russia). Patients with ejection fraction < 40%, atrial fibrillation and severe comorbidities were not included. 24-h, awake and sleep-time systolic, diastolic and pulse blood pressure in aorta and brachial artery were compared in subgroups divided according to the diurnal pattern of brachial systolic blood pressure (SBP). Results: The diurnal profiles of central systolic and pulse BPs run in parallel with those of peripheral BPs in patients with all types of diurnal pattern and SBP amplification at night did not change significantly comparing to day-time values. Non-dipping or reverse-dipping SBP patterns appeared to be typical and were observed in 82, 1% patients, while 50, 7% participants had inadequate DBP dip < 10%. The proportionality of night-time SBP and DBP changes varied in different types of SBP diurnal profile. SBP and DBP decreased proportionally in dippers (ratio of DBP/SBP night-time reduction was 1, 18) and disproportionately in non-dippers (the ratio was 2, 6). In those patients with reverse-dipping pattern SBP and DBP changed in opposite directions at night. This disproportion in SBP and DBP night-time changes resulted in different intensity of PP night-time rise that was most evident in reverse-dippers. Relative nocturnal reduction of PP was 9, 3 ± 4, 72% in dippers, whereas non-dippers and reverse-dippers had relative PP increase of 6, 2 ± 8, 6 and 22, 9 ± 12, 3 %, respectively. Conclusions: The diurnal patterns of central and brachial BPs observed in very elderly treated hypertensives were almost parallel. PP amplification is similar in the day- and nighttime and this finding is different from previously described diurnal PP amplification behavior in younger subjects. Proportionality of SBP and DBP sleep-time changes depends on dipping status and results in nocturnal PP increase in non- and reverse-dippers.